A CORRELATIVE STUDY OF STUDENTS’ MOTIVATION, VOCABULARY MASTERY AND READING COMPREHENSION - Husni, Rauldatul (RC-INSTITUT, 2018)
This research aimed to find the correlation among students’ motivation, vocabulary mastery and reading comprehension of the students four semester at Universitas Dharmas Indonesia in academic year 2017-2018. Motivation is the key factor in learning any language, especially in reading. Learning motivation influences the student’s interest and learning result. A person who has high motivation in reading will also has high interest in reading. It is based on the belief that the success and effectiveness of the teacher rest upon producing learner who are proficient and smart readers. Hence, the researcher is greatly challenged to conduct this research. The Correlative method was used in this research. It was used to find out the relationship of students’ motivation, vocabulary mastery and reading comprehension. A questionnaire and tests were used in collecting the data. They consisted of the students’ motivation questionnaire, reading test and vocabulary test. The statistical tools used in analyzing the data in this study were Descriptive Statistics and Pearson Product-Moment Correlation. The findings of the research were the students’ level in reading comprehension of the students’ four semester at Universitas Dharmas Indonesia was very good. The students’ level in vocabulary was poor. The students need to improve their vocabulary in order to comprehend the text. Moreover, the students four semester at Universitas Dharmas Indonesia were motivated in reading comprehension. There was a significant correlation among reading comprehension, vocabulary mastery and students’ motivation. In improving the students’ reading comprehension, the teacher should teach vocabulary to their students since vocabulary has strong relationship with reading comprehension. Having a good vocabulary makes the students understand the text easily. Vocabulary mastery is more important in helping the students to comprehend the text. Besides, motivation is also a key factor in reading comprehension. Motivation correlates significantly with the reading achievement. The students who are highly motivated will get better achievement in reading than those who are low or less motivated.   Keywords: students’ motivation,vocabulary mastery, reading comprehension.